ANALISIS MUTU KUE BANGKIT BAHAN BAKU UBI JALAR (Ipomea batatas L) SEBAGAI MP-ASI - Imelda Fitri; Hotmauli Hotmauli; Nurul Badriyah; Citra Dewi Anita Sari (LPPM Universitas Abdurrab, 2023)
Early 6 months of age are given complementary feeding. MP-ASI is carried out in stages, starting from soft, and solid foods at the age of 1 year. The basic ingredients of kue bangkit is tapioca flour. New innovations are needed as substitute for tapioca flour, purple sweet potato is a safe local food. The study's goal was to determine the quality kue bangkit (yield, moisture content, macro and micronutrient) levels of sweet potato flour as a raw material for rose cakes used for complementary feeding.The research method used was a laboratory experiment involving the analysis of the levels yield, moisture content, macro and micro nutrient) sweet potato flour. Based on the yield analysis purple sweet potato at 27%, low water content, the macro and micronutrient content were namely, fat content 15.12%, protein 5.03%, carbohydrates 42.44%, moisture content 8.19%, ash content 2.44%, iron 27.78 mg/kg, and zinc 13.60 mg/kg. This shows that kue bangkit purple sweet potato can be used as the latest innovation as an SNI standard MP-ASI.